Islam and progress - Altabaa, Homam (2021)
This study explores the concept of progress from an Islamic perspective. It begins by highlighting the importance of analyzing the historical development of ideas in all human civilizations. Subsequently, the study examines the relationship between religion and science and the evolution of major ideas such as humanism and modernity. The focus is narrowed down to Islam and its conception of science and progress, especially its philosophies of self-development, social development and comprehensive excellence. In its final analysis, the study shifts to compare and contrast various worldviews and their interaction with religion in the contemporary world. The ideas of secularism and secularization are examined from the perspective of Islam and progress. All in all, the study relies on studies by Ernest Gellner, Linda Woodhead and Jordan Peterson as its frame of reference.